1962
DOI: 10.1080/17470216208416542
|View full text |Cite
|
Sign up to set email alerts
|

Eliminative and Enumerative Behaviour in a Conceptual Task

Abstract: P. C. Wason's paper “On the Failure to Eliminate Hypotheses in a Conceptual Task” is criticized on the grounds that the task set is in important respects untypical of problem solving situations in general. It is suggested that few or no subjects are “Eliminators” in Wason's sense and that although many are “Enumerators” in his sense, enumerative behaviour is a function of the situation. An experiment is reported in which it appears that modification to the situation can sharply reduce the incidence of enumerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
44
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 1 publication
0
44
0
Order By: Relevance
“…This issue is reminiscent of early discussions of the rule-discovery task (Wetherick, 1962;Wason, 1962) in which a distinction was drawn between falsification of a hypothesis explicitly considered by a participant (falsification in H E ), and the kind of implicit falsification that occurs because the oracle's responses are inconsistent with a great many rules, regardless of whether the learner has explicitly considered them (falsification in H I ). The analysis in this paper treats both of these events as genuine falsifications, even though the learner would be unaware of implicit falsifications.…”
Section: Implicit Falsification and The Role Of Memorymentioning
confidence: 99%
“…This issue is reminiscent of early discussions of the rule-discovery task (Wetherick, 1962;Wason, 1962) in which a distinction was drawn between falsification of a hypothesis explicitly considered by a participant (falsification in H E ), and the kind of implicit falsification that occurs because the oracle's responses are inconsistent with a great many rules, regardless of whether the learner has explicitly considered them (falsification in H I ). The analysis in this paper treats both of these events as genuine falsifications, even though the learner would be unaware of implicit falsifications.…”
Section: Implicit Falsification and The Role Of Memorymentioning
confidence: 99%
“…In particular, such coding is insensitive to participants' expectations about test outcomes (Poletiek, 1996); for example, a triple receiving positive feedback may have been generated with falsification in mind (Wetherick, 1962; see also Caverni & Rossi, 1997, for corroboration of Wetherick's proposal). In this paper we avoid labelling triples as either confirmatory or disconfirmatory, and instead follow others (e.g., Oaksford & Chater, 1994;Valle´e-Tourangeau et al, 1995) who simply code triples as either ''positive'' or ''negative'' (i.e., conforming or not conforming to the experimenter's rule).…”
mentioning
confidence: 93%
“…Notwithstanding concerns that have been voiced in the literature over Wason's confirmation-bias account of the 2-4-6 task (Evans, 1989;Klayman & Ha, 1987), there is little doubt that the initial 2-4-6 triple provides a compelling lure that encourages formulation of overly narrow initial hypotheses (Wetherick, 1962). In a recent study, for example, Cherubini et al (2005) showed that participants derive initial hypotheses that retain the relational regularities that are salient in the 2-4-6 triple, since such regularities have high ''information relevance'' (see also Van der Henst et al, 2002, for further demonstrations of ''relevance effects'' arising with the 2-4-6 triple).…”
mentioning
confidence: 94%
“…Early criticism of Wason's (1960) "confirmation bias" account came from Wetherick (1962), who claimed that it was simply the experimenter's essentially devious provision of the 2-4-6 exemplar triple that lured participants into the production of the overly restricted hypotheses that are commonly announced. More recent support for Wetherick's proposal has come from research by Van der Henst, Rossi, and Schroyens (2002), who invoked "relevance theory" (e.g., Sperber, Cara & Girotto, 1995) to argue that participants expect that the information provided by the presented seed triple will be of value for solving the task.…”
mentioning
confidence: 99%